The intercultural experiences of Vietnamese students in Taiwan: A transformative learning analysis of written reflections - Jade, Nguyen-B-Ngoc; Nakazawa, Kazuaki; Ke, I-Chung (Journal of International Students, 2026)
This study explores the intercultural experiences of four Vietnamese students in a Taiwanese intercultural communication course over 15 weeks of self-reflective writing. Guided by Mezirow’s transformative learning theory, this analysis examines how these students navigate cultural differences, make sense of stereotypes, and reconstruct their identities. Qualitative analysis reveals disorienting dilemmas, critical reflection, and shifts in perspective that deepen cultural awareness and empathy. Self-reflective writing has emerged as a crucial tool for expressing and connecting classroom discussions with personal experiences. The findings highlight the importance of experiential learning and reflection in promoting intercultural sensitivity, offering valuable insights for curriculum design in global education settings.